Longitudinal overview of digital and media literacy: A taxonomy-based research trends analysis from 1954 to 2023 - Andrade Girón, Daniel Cristóbal; Zúñiga Rojas, Marcelo Gumercindo; Lioo Jordán, Flor de María; Vellón Flores, Viviana Inés; Garivay Torres de Salinas, Flor de María; Solano Armas, Timoteo (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. A longitudinal analysis was performed to explore the thematic composition of digital and media literacy and define a taxonomy. A generic taxonomy was established in the initial phase, followed by a sub-period taxonomy. This approach facilitated an understanding of the evolution of this field over time. Design/Methodology/Approach. A total of 11,066 documents were retrieved from Scopus composed the sample. The longitudinal analysis was generated from the defined time coverage, which spanned the period from 1954 to 2023. We considered the division into four subperiods: 1954-1979, 1980-1999, 2000-2009, and 2010-2023. A taxonomy was constructed using the clustering results and the most frequent top terms. The taxonomy was structured hierarchically, with more generic categories and subcategories positioned below them. Results/Discussion. The general taxonomy comprised five categories: (1) digital literacy and competencies, (2) media literacy and empowerment, (3) digital and media literacies in educational contexts, (4) social impact of literacy, and (5) validation and development. In the initial sub-period (1954-1979), there was an early focus on developing general literacy, media skills, and business-related competencies. During the second sub-period (1980-1999), there was a notable shift in focus towards education, computer literacy, and increasing technology integration in the educational setting. During the third subperiod (2000-2009), the prominence of digital and media literacy issues increased. In the final sub-period (2010-2023), there is evidence of a greater focus on digital skills, big data, and social media literacy. A notable shift towards a greater emphasis on research and the utilization of ICT in education reflects the advent of a fully-fledged modern information age. Conclusions. A comprehensive examination of the taxonomy groups reveals many themes, including the personal empowerment of digital literacy and establishing institutional frameworks to validate educational models. Each group encapsulates a particular facet of media, digital, and social literacy while elucidating the broader societal ramifications of these literacies. This analysis demonstrates a progression from general literacy concepts in the early periods to an increasing focus on digital and media literacy in the most recent years.